Сленг соціальних мереж як проблема сучасних мовознавчих та перекладознавчих досліджень - Косенко, А.В.; Сорочан О.В.; Дідковська, Т. Л. (My University, 2026)
The relevance of the study is due to the fact that slang is one of the most striking manifestations of language dynamics, reflecting informal communication within different social groups. In modern linguistics, slang is considered as a special lexical category that combines emotional expressiveness, familiarity and predominant use in oral speech. Its variability, close connection with the sociocultural context and the ability to quickly respond to social changes make slang a complex but extremely valuable object of linguistic analysis. It is proven that one of the defining features of slang is its social conditioning. Slang is formed within certain social groups, such as youth subcultures, professional communities or marginal environments, and reflects their values, way of thinking and cultural priorities. In this context, slang acts not only as a lexical phenomenon, but also as a cultural marker that emphasizes group identity. It is assumed that vocabulary originating from the youth environment often becomes more widely used, losing its original meaning or acquiring new semantic shades. Such semantic variability is a key characteristic of slang, which complicates its systematization, but at the same time makes it an important source for the study of linguistic creativity. It is noted that social networks are a unique environment that shapes the linguistic reality of the 21st century. It is concluded that slang, which arises and functions in this space, reflects the desire for identity, expressiveness and efficiency. Its semantic variability and cultural diversity make social media an ideal subject for linguistic analysis, allowing for a deeper understanding of how language adapts to the challenges of the digital age. At the same time, the rapid variability and ambiguity of slang create challenges for its study, requiring a combination of traditional and modern methods.
Keywords: slang, social media, lexical paradigm, jargon, argot, colloquialisms, semantics, sema, structural features.